Acute Erythroid Leukemia (AML-M6a) of protracted onset in a child: Evolution from pre-existing MDS or de novo entity - Rama Kumari Badyal; Navneet Kaur; Amrinder Kaur; Monika Garg (GMC Patiala Journal of Research and Medical Education, 2021)
Acute erythroid leukemia is a heterogenous disease, which may arise de novo, secondary to MDS (myelodysplastic syndrome) or after cytotoxic therapy. Pediatric erythroleukemia is an acute onset leukemia which is usually diagnosed within 1-2 months after the onset of symptoms. Patients very rarely present with symptoms lasting longer than 6 months. Here is a case of erythroleukemiain a child of age 10 years, who presented with low grade fever, severe pallor and hepatosplenomegaly for 12 months duration. Peripheral smear examination showed anemia, thrombocytopenia,nucleated red blood cells and circulating blasts. The bone marrow displayed erythroid hyperplasia with dysplasiaand presence of myeloid blasts which showed auer rods and myeloperoxidase positivity. Immunophenotypic characterization by flow cytometryrevealed myeloid and erythroidprecursors. Hence a diagnosis of erythroleukemia was made. The case is being discussed here because of its rarity and unusual presentation with such long clinical history and its probable evolution from pre-existing MDS.